Covid-19: scienza e comunicazione nell’emergenza pandemica. C’è qualcosa di peggio delle fake news? - Tagliamonte, Rosa (Teoria e Critica della Regolazione Sociale / Theory and Criticism of Social Regulation, 2023)
The topic of Covid-19 has a key role in the public debate. The complexity of medical science and the consequences that its applications can have, put considerations concerning the responsibility of the scientific community and the communication of their results to the society. In this scenario, the public communication system has the social responsibility to give information to the people about the benefits and risks of the decisions relating to the pandemic emergency, the scientific development and its practical applications: the vaccine. The issue of anti Covid-19 vaccinations divides public opinion and politicians between supporters and no-vax, with protests and threats via social media to virologists, politicians and journalists. This contribution intends to offer a starting point for discussion on the role played by the media and social media in our society during the pandemic, and on the social perception of the risk associated with the Covid-19 vaccine in Italy.